STUDIES ON CROP BEHAVIOUR AND PRODUCTIONS OBTAINED IN SUMMER CROP FOR WHITE CABBAGE HYBRIDS - Nicoleta OLTENACU; Elena LASCAR; Mariana NASTASE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Since cabbage is a product frequently used in feeding the population, we tried that through the research made to find hybrids that correspond regarding the yields obtained but also from qualitative point of view, according to the market requirements. The purpose was to analyze the behaviour of some hybrids recommended by different producers in terms of climate and soil conditions found in Dâmboviţa county and in climatic conditions of 2014, following the results we can make recommendations that can be put into practice and that can satisfy the producers both from the point of view of the production potential and from the point of view of inputs needed for its maximization. The behaviour of five hybrids was studied, suitable for field crop: Cheers, Taurus, NIZ 17-1197, NIZ 17-1043, Mighty Boy. Very significant increases compared to the control were achieved by NIZ hybrids range. Unsalable leaf production reached the highest value in Taurus hybrid, 408.8 g, with the average production over 85.52 g and 93.8 g, over control production, these values mean increases of over 25%. From the economic point of view, the crop is a profitable one, the expense is lower than the revenue. Therefore, after analyzing the behavior of the hybrids used in experience on the existing soil in Damboviţa county region, we can say that all studied hybrids showed good results. The highest productions and the highest production increases, for summer crop, were obtained by Taurus NIZ 17-1197 and 17-1043 NIZ hybrids.